PROMIS Function Scores Are Lower in Patients Who Underwent More Aggressive Local Treatment for Desmoid Tumors. Issue 3 (March 2020) - Newman, Erik T.; Lans, Jonathan; Kim, Jason; Ferrone, Marco; Ready, John; Schwab, Joseph; Raskin, Kevin; Calderon, Santiago Lozano
Abstract: Background: Desmoid tumors of the extremities often present with pain and functional limitation, but treatment can lead to morbidity and recurrence is common. The impact of treatment with respect to traditional "oncologic" metrics (such as recurrence rate) has been studied extensively, with a shift in recent years away from local therapies as first-line management; however, little is known about the association between treatment modality and long-term functional outcomes for patients with this benign disease. Questions/purposes: In a retrospective review of consecutive patients treated at two institutions, we asked: (1) Is event-free survival (EFS) different between patients who undergo local treatment and those who do not for primary as well as for recurrent desmoid tumors? (2) What treatment-related factors are associated with worse Patient-reported Outcomes Measurement Information System (PROMIS) function scores at a minimum of 1 year after treatment? Methods: Between 1991 and 2017, 102 patients with desmoid tumors of the extremities (excluding those of the hands and feet) were treated at two institutions; of those, 85 patients with 90 tumors were followed clinically for at least 1 year (median [range] 59 months follow-up [12 to 293]) and were included in the present analysis. We attempted to contact all patients for administration of PROMIS function (Physical Function Short Form [SF] 10a and Upper Extremity SF v2.0 7a) and Pain Interference (SF 8a) questionnaires. Complete survey data (minimum 1 year follow-up) were available for 46% (39 of 102) of patients with 40 tumors at a median of 125 months follow-up; only these patients were included in PROMIS data analyses. Though there was no formal institutional treatment algorithm in place during the study period, surgical resection typically was the preferred modality for primary tumors; radiation therapy and systemic treatments (including cytotoxic or hormonal agents earlier in the study period, and tyrosine kinase inhibitors later) were often added for recurrent or very symptomatic disease. We coded treatment for each patient into discrete episodes, each defined by a particular treatment strategy: local treatment only (surgery and/or radiation), systemic treatment only, local plus systemic treatment, or observation; treatment episodes rendered at other institutions (that is, before referral) were not included in the analyses. Treatment failure was defined as recurrence after surgical resection, or clinically significant radiologic and/or symptomatic progression after systemic treatment, and EFS was defined as time from treatment initiation to treatment failure or final follow-up. Episodes of treatment for recurrent tumors were analyzed in a pooled fashion, wherein discrete treatment episodes for patients with multiple recurrences were included separately as independent events. We analyzed 56 primary tumors (54 patients), and 101 discrete treatment episodes for recurrent tumors (88 patients). Kaplan-Meier survival curves were constructed separately for the primary and recurrence cohorts, both comparing EFS among patients who received any local treatment (local treatment and local plus systemic treatment groups) versus those who did not (systemic treatment and observation groups). PROMIS function data were analyzed on the bases of patient- and treatment-specific variables, including the PROMIS Pain Interference score as a potential explanatory variable. Results: Within both the primary and recurrence cohorts, there were no differences between the local treatment, systemic treatment, and local plus systemic treatment groups with respect to gender, age, axillary/hip girdle location, or tumor volume. Among primary tumors, 5-year EFS was 44% (95% CI 24 to 80) for the systemic-only group versus 15% (95% CI 5 to 44) for the local treatment group (p = 0.087). Within the pooled recurrence treatment episode cohort, 5-year EFS after systemic-only treatment was 70% (95% CI 52 to 94) versus 56% among patients receiving any local treatment (95% CI 44 to 70; p = 0.46). PROMIS function scores were lowest among patients who underwent two or more resections (39 versus 51 versus 47 for ≥2, 1, and 0 resections, respectively; p = 0.025); among those who received both surgery and radiation at any point, either concurrently or in separate treatment episodes, as compared with those who did not (39 versus 46; p = 0.047); and among those with higher levels of pain interference (38 versus 47 for pain interference scores > 50 versus < 50; p = 0.006). Conclusions: Patients treated with local modalities (surgery and/or radiation, with or without additional systemic therapy) did not experience improved EFS as compared with those treated without local modalities; this was the case for both the primary and the recurrent tumor cohorts. However, PROMIS function scores were lowest among patients who underwent two or more surgical interventions and among those treated with surgery and radiation at any time, suggesting that more aggressive local treatment may be associated with poorer long-term functional outcomes. Prospective collection of patient-reported outcomes data at multiple time points will allow for more direct correlations between treatment modality and impact on function and will help to elucidate the ideal management strategy for these benign but often-symptomatic tumors. Level of Evidence: Level III, therapeutic study.